Demographic factors influencing the buying process : online consumers from Denmark and Iceland - Gylfi Aron Gylfason 1986- (2011)
Recent developments have shown that U.S. online retailers have started to internationalize through global e-commerce as a result of buyer demand for lower prices and greater product availability. These firms though continue to struggle with how to effectively market to these online buyers as they vary greatly in terms of their consumer behavior and buying process. Past research on online consumer behavior has mainly focused on consumers purchasing products domestically, with scarce research on those purchasing products internationally. Therefore, this study chose to focus on online consumers from Denmark and Iceland who are purchasing products from U.S. online retailers. These consumers were surveyed in order to gain insight into the influence of various demographic factors—including gender, age, and income—on their buying process. The results indicated vast differences between these demographic segments, especially in regards to gender. The findings of this research inform marketers how to plan and align their marketing activities in order to attract various demographic segments from Denmark and Iceland. Furthermore, this research contributes to Kotler’s framework on the forces influencing the buying process. ShopUSA